Whole genome characterization and evolutionary analysis of G1P[8] rotavirus a strains during the pre-and post-vaccine periods in mozambique (2012–2017) - Munlela, Benilde (2020)
Mozambique introduced the Rotarix® vaccine (GSK Biologicals, Rixensart, Belgium) into the National Immunization Program in September 2015. Although G1P[8] was one of the most prevalent genotypes between 2012 and 2017 in Mozambique, no complete genomes had been sequenced to date. Here we report whole genome sequence analysis for 36 G1P[8] strains using an Illumina MiSeq platform. All strains exhibited a Wa-like genetic backbone (G1-P[8]-I1-R1-C1-M1-A1-N1-T1-E1-H1). Phylogenetic analysis showed that most of the Mozambican strains clustered closely together in a conserved clade for the entire genome. No distinct clustering for pre-and post-vaccine strains were observed. These findings may suggest no selective pressure by the introduction of the Rotarix® vaccine in 2015. Two strains (HJM1646 and HGM0544) showed varied clustering for the entire genome, suggesting reassortment, whereas a further strain obtained from a rural area (MAN0033) clustered separately for all gene segments. Bayesian analysis for the VP7 and VP4 encoding gene segments supported the phylogenetic analysis and indicated a possible introduction from India around 2011.7 and 2013.0 for the main Mozambican clade. Continued monitoring of rotavirus strains in the post-vaccine period is required to fully understand the impact of vaccine introduction on the diversity and evolution of rotavirus strains.